Atmospheric Forcing of the Pacific Meridional Mode: Tropical Pacific‐Driven Versus Internal Variability. Issue 7 (5th April 2022) - Zhang, Yu; Yu, Shi‐Yun; Amaya, Dillon J.; Kosaka, Yu; Stuecker, Malte F.; Yang, Jun‐Chao; Lin, Xiaopei; Fan, Lei
Abstract: The Pacific Meridional Mode (PMM) impacts tropical Pacific sea surface temperature variations, which in turn affect the PMM through the excited atmospheric teleconnections. Previous studies linked this loop to the tropical Pacific‐excited North Pacific Oscillation (NPO; the second empirical mode of North Pacific sea level pressure variability), while a recent study proposed the linkage to the excited Aleutian low (AL) variability (the first empirical mode). Unraveling their relative importance for the loop is thus crucial for better understanding subtropical‐tropical interactions. Here, using tropical Pacific pacemaker experiments we show that tropical Pacific‐forced AL variability is tied to the loop, while the tropical Pacific‐forced NPO does not effectively induce PMM variability, hence not being in the loop. Our study emphasizes the role of tropical Pacific‐forced AL variability in the PMM‐tropical Pacific interaction, which should be paid more attention in future studies. Plain Language Summary: The Pacific Meridional Mode (PMM) is a prominent pattern of climate variability situated in the subtropical northeastern Pacific. Sea surface temperature (SST) anomalies associated with the PMM can propagate into the deep tropics via a feedback process involving the coupling between wind, evaporation, and SST. In the tropics, these SST anomalies can induce a response of the extratropical atmospheric circulation—so‐called teleconnections—which in turn can induce PMM variability via the effect of this anomalous atmospheric circulation on surface heat fluxes in the subtropics. Previous studies linked the tropical‐to‐subtropical teleconnection in this loop to the second leading statistical pattern of North Pacific atmospheric variability—the so‐called North Pacific Oscillation. However, a recent study pointed out that this tropical‐to‐subtropical teleconnection is also associated with prominent anomalies of the Aleutian low (AL)—the first leading statistical pattern of North Pacific atmospheric variability. To reveal which dominant pattern of atmospheric variability is primarily tied to the teleconnection, we quantify their relative role in causing PMM variability based on climate model simulations. We find that AL variability plays the key role in linking the tropics with the subtropics. Key Points: Internal Aleutian low (AL) variability is displaced northward compared to tropically forced AL variability, thus ineffectively forcing the Pacific Meridional Mode (PMM) Internal North Pacific Oscillation and North Pacific Tripole variabilities are stronger than their tropical Pacific‐driven counterparts, hence contributing to forcing the PMM Tropical Pacific‐driven AL variability links the interaction between the PMM and tropical Pacific sea surface temperature variations